Nuclear localised more sulphur accumulation1 epigenetically regulates sulphur homeostasis in Arabidopsis thaliana - Huang, Xin-Yuan; Chao, Dai-Yin; Koprivova, Anna; Danku, John; Wirtz, Markus; Müller, Steffen; Sandoval, Francisco J.; Bauwe, Hermann; Roje, Sanja; Dilkes, Brian; Hell, Rüdiger; Kopriva, Stanislav; et al. (Public Library of Science, 2016)
Sulphur (S) is an essential element for all living organisms. The uptake, assimilation and metabolism of S in plants are well studied. However, the regulation of S homeostasis remains largely unknown. Here, we report on the identification and characterisation of the more sulphur accumulation1 (msa1-1) mutant. The MSA1 protein is localized to the nucleus and is required for both S adenosylmethionine (SAM) production and DNA methylation. Loss of function of the nuclear localised MSA1 leads to a reduction in SAM in roots and a strong S-deficiency response even at ample S supply, causing an over- accumulation of sulphate, sulphite, cysteine and glutathione. Supplementation with SAM suppresses this high S phenotype. Furthermore, mutation of MSA1 affects genome-wide DNA methylation, including the methylation of S-deficiency responsive genes. Elevated S accumulation in msa1-1 requires the increased expression of the sulphate transporter genes SULTR1;1 and SULTR1;2 which are also differentially methylated in msa1-1. Our results suggest a novel function for MSA1 in the nucleus in regulating SAM biosynthesis and maintaining S homeostasis epigenetically via DNA methylation.